2017
DOI: 10.18632/oncotarget.21421
|View full text |Cite
|
Sign up to set email alerts
|

Targeting aggressive prostate cancer-associated CD44v6 using phage display selected peptides

Abstract: There is a crucial need to identify new biomarkers associated with aggressive prostate cancer (PCa) including those associated with cancer stem cells (CSCs). CD44v6, generated by alternative splicing of CD44, has been proposed as a CSC biomarker due to its correlation with aggressive PCa disease. We hypothesized that phage display selected peptides that target CD44v6 may serve as theranostic agents for aggressive PCa. Here, a 15 amino acid peptide (“PFT”) was identified by affinity selection against a peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
(86 reference statements)
0
10
0
3
Order By: Relevance
“…In addition to the targeting of the pro-survival and selfrenewal pathways, some novel therapeutic strategies are based on the immunologic targeting of PCa-and PCSC-specific markers such as CD44, prostate stem cell antigen (PSCA), and ALDH. To target CSC marker CD44, recent studies used phage display library to identify high affinity peptide that target CD44v6 protein isoform and can be potentially used for systemic delivery of diagnostic and therapeutic molecules in PCa patients [174]. Several other studies demonstrated potential application of anti-CD44 antibodies to target CSC cells in acute myeloid leukemia (AML) and pancreatic xenograft models as reviewed in [175].…”
Section: Genetic Evolvingmentioning
confidence: 99%
“…In addition to the targeting of the pro-survival and selfrenewal pathways, some novel therapeutic strategies are based on the immunologic targeting of PCa-and PCSC-specific markers such as CD44, prostate stem cell antigen (PSCA), and ALDH. To target CSC marker CD44, recent studies used phage display library to identify high affinity peptide that target CD44v6 protein isoform and can be potentially used for systemic delivery of diagnostic and therapeutic molecules in PCa patients [174]. Several other studies demonstrated potential application of anti-CD44 antibodies to target CSC cells in acute myeloid leukemia (AML) and pancreatic xenograft models as reviewed in [175].…”
Section: Genetic Evolvingmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41] Indeed, is there any limit to the number of different ligands, some perhaps of great practical worth, that might evolve from the very same library by imposing different selection regimes, without the need for deep prior knowledge?Members of the phage-display community have constructed many additional libraries of innovative design, from which many valuable ligands have been selected, including the therapeutic antibodies described in WintersNobel lecture. [33][34][35][36][37][38][39][40][41] Indeed, is there any limit to the number of different ligands, some perhaps of great practical worth, that might evolve from the very same library by imposing different selection regimes, without the need for deep prior knowledge?Members of the phage-display community have constructed many additional libraries of innovative design, from which many valuable ligands have been selected, including the therapeutic antibodies described in WintersNobel lecture.…”
Section: In Vitro Evolution Of S-peptide Antagonists By Affinity Matumentioning
confidence: 99%
“…Theligands Yu discovered have no known practical worth apart from their heuristic value.B ut ligands for other, pharmacologically significant selectors have been affinityselected from the same library,including in the lab of my longtime University of Missouri colleague Sue Deutscher. [33][34][35][36][37][38][39][40][41] Indeed, is there any limit to the number of different ligands, some perhaps of great practical worth, that might evolve from the very same library by imposing different selection regimes, without the need for deep prior knowledge?Members of the phage-display community have constructed many additional libraries of innovative design, from which many valuable ligands have been selected, including the therapeutic antibodies described in WintersNobel lecture. [32]…”
Section: Nobel Lecturesmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41] Es stellt sich die Frage,o be se ine Grenze fürd ie Zahl unterschiedlicher Liganden gibt, von denen manche vielleicht große praktische Bedeutung haben, die sich aus der gleichen Bibliothek entwickeln, indem man, ohne vorher fundierte Kenntnisse zu bençtigen, unterschiedliche Selektionsarten anwendet. Ausderselben Bibliothek wurden jedoch Liganden füra ndere,p harmakologisch wichtige Selektoren affinitätsselektioniert, darunter im Labor meiner langjährigen Kollegin Sue Deutscher von der University of Missouri.…”
Section: Affinitätsselektion Aus Zufallspeptid-bibliothekenunclassified
“…Ausderselben Bibliothek wurden jedoch Liganden füra ndere,p harmakologisch wichtige Selektoren affinitätsselektioniert, darunter im Labor meiner langjährigen Kollegin Sue Deutscher von der University of Missouri. [33][34][35][36][37][38][39][40][41] Es stellt sich die Frage,o be se ine Grenze fürd ie Zahl unterschiedlicher Liganden gibt, von denen manche vielleicht große praktische Bedeutung haben, die sich aus der gleichen Bibliothek entwickeln, indem man, ohne vorher fundierte Kenntnisse zu bençtigen, unterschiedliche Selektionsarten anwendet. Phagen-Display-Forscher haben viele weitere Bibliotheken nach innovativen Plänen entworfen, aus denen viele wertvolle Liganden selektioniert wurden, darunter auch die therapeutischen Antikçrper, die in Winters Nobelvortrag beschrieben wurden.…”
Section: In-vitro-evolution Von S-peptid-antagonisten Durch Affinitätunclassified